Motivation and competence on the performance of employees in the procurement of goods and services at the Regional Secretariat - Government of Berau Regency - Puspita, Agnes Alvin Dhian; Alaydrus, Anwar; Darmayanti, Tri (Technium Social Sciences Journal, 2021)
Employee performance appraisal is a very important thing in an organization to achieve its goals, so that the organization must carry various policies out to improve employee performance. The purpose of this study was to analyze the influence of motivation and competence in performing the employees of the Service Procurement Service at the Regional Secretariat – Government of Berau Regency. We designed the study with primary data sources through interviews with thirty-one respondents or employees. Then, the data processed using the multiple linear regression analysis model through the IBM SPSS 24. Empirical findings revealed that motivation partially had a positive and significant effect on employee performance, competence partially had a positive and significant effect on performance, and competence is a variable that has a dominant influence on employee performance.